Wind turbine plate thickness design optimization - Jumhur, Aam Amaningsih; Sirojuddin, .; Suharjo, Haryo; Wulandari, Dyah Arum; Nur Najmiyah, Jaafar (Penerbit UMP, 2024)
The design of the blade thickness of the Darrieus wind turbine should be optimized. This study aims to obtain the optimal thickness of the blade plate so that its weight and strength can be optimal. The design begins with preliminary calculations to find the optimal dimensions based on a wind speed of 15 m/s. The blade design was drawn in 2D using AutoCAD software, followed by 3D manufacturing, and material stress analysis was carried out with Autodesk Inventor software. The optimization of the yield stress value compared to the applied stress is 3.0. The software simulation of stress analysis results found that the most optimal thickness was 0.2 mm at variant B-3.